Comparison of the results of the study of cellular technologies in the treatment of ischemic cardiomyopathy in different epochs of drug therapy (Bangladesh Journal of Medical Science, 2025)
Background Currently, it is obvious that stem cell therapy opens up prospects for the treatment of certain diseases, but at the same time it faces serious problems. First, most clinical data indicate a positive effect of stem cell transplantation on heart repair, regardless of cell types and methods of their delivery. Objectives Comparison of the results of the study of cellular technologies in the treatment of ischemic cardiomyopathy in different epochs of drug therapy Methods The researched studies obtained from the PubMed and Scopus Preview databases are presented in two tables. The first table shows the studies of group “A” for the period 2004-2010. Results The results of the studies of the first group “A” (2004-2010) were as follows: in studies like T. Siminiak et al. (2004), N.Dib et al. (2005), A.A. Hagege et al. (2006), M. Haack‐ Sorensen et al. (2008) (MSC-HF), Hare J.M. et al. (2009), Assmus B. et al. (2010), Strauer B.E. et al. (2010) (STAR- heart research); Wang S. and co-author. (2010), Mansour S. et al. (2010) (COMPAREAMI study) stem cells used in ischemic cardiomyopathy had a positive effect on the myocardium. Conclusion The results of the analysis of the studies showed the following: given the changes in the tactics of drug therapy of CHF over time, there was no significant difference in the results between the two groups of studies on the use of stem cells in ischemic cardiomyopathy.Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 554-559